Risk Factors and Fetal Outcome of PE Cases in a Tertiary Level Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Objective: To study the risk factors and foetal outcome of pre-eclampsia in a tertiary level hospital.Materials and methods: A total 40 consecutive patients of pre-eclampsia (PE) were included in this study between April 2009 to March 2010. Patients whose B.P. was ³140/90 mm of Hg and proteinuria detected by dipstick test were included in this study. Detailed discussion about the study was done with the patient and then written informed consent was taken from them. Detailed history about patient profile, risk factors and foetal outcome in terms of birth weight, maturity and IUGR(intrauterine growth retardation) etc were recorded in predesigned data collection sheet. Data was expressed in terms of frequenies and percentages.Results: Most of the patients were in the age group of 20-30 years (52.5%) and 60% were primi gravida . Most of the patient (60%) developed pre-eclampsia at 37 weeks of gestation. Regarding risk factors 30% patients were obese, previous history of pre-eclampsia (PE) in 7.5% cases, pregnancy with diabetes was found in 5% cases and multiple pregnancy in 2.5% cases. Caesarean section was done in 72.5% cases and vaginal delivery occurred in 25% cases. Birth weight 2.5-3 kg found in 40% cases. 37.5% babies were premature, IUGR in 7.5%, intrauterine death in 5% and neonatal death was observed in 2% cases.Conclusion: Primi gravida are more prone to develop pre-eclampsia. Obesity, previous history of pre-eclampsia, multiple pregnancy and pregnancy with diabetes mellitus increase the risk of pre-eclampsia. Prematurity, intrauterine growth retardation (IUGR), intrauterine death (IUD), neonatal death are important foetal complications.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 3-7